Jumping abilities and power-velocity relationship in judo athletes: Comparative analysis among age categories - Busko, K. (Human Movement, 2015)
Purpose. The aim of the study was to examine age differences in the maximal power and height of rise of the body mass centre measured in spike jump (SPJ) and counter-movement jump (CMJ), and power-velocity relationship of lower extremities between cadet and U23 age class judo athletes. Methods. Seven cadets (age 16.6 ± 0.7 years) and eight U23 age class (21.3 ± 1.4 years) Polish judoists took part in the study. The maximal power and height of jump were measured at SPJ and CMJ jumps. Power- velocity relations (P-v) were determined from 5 maximal cycle ergometer exercise bouts at increasing external loads equal to 2.5, 5.0, 7.5, 10.0 and 12.5% of body weight (BW). Results. Cadet judoists had a significantly smaller maximal power output (11.56 ± 1.21 W · kg-1) than U23 athletes (12.69 ± 0.67 W · kg-1). The optimal velocity was similar in both group (119.3 ± 16.0 rpm and 119.6 ± 15.5 rpm, respectively). Significant age differences were founded between the cadet and U23 athletes for power output at external load equal 12.5% BW. Cadet judoists generated insignificantly lower maximal power in CMJ and SPJ than U23 judo athletes with except of the absolute maximal power in SPJ. The age difference was observed in height of CMJ. Conclusions. Based on the characteristics of F-v curve we can see in which direction follow the effects of training. Application of CMJ and SPJ in jumping test allows to assess changes in neuromuscular coordination. The use of the both methods give better information to optimal training control.